La dialéctica eticidad-moralidad-acción en la formación universitaria: el esfuerzo de la negación - Yurén Camarena, Teresa (Revista Internacional de Teoría e Investigación Educativa, 2024)
The aim of this article is to provide reasons to sustain that making socio-moral formation effective requires considering the dialectic ethicity-morality-action, in which the "effort of negation" is indispensable. The terms included in this thesis, constructed on the basis of classical and current authors, are clarified and some paradoxical implications of this dialectic are shown, as well as the aspects in which the effort of negation is required. The need to make a critique of the hegemonic ethicity in which values and pseudo-values are interwoven is shown; the idea that uncertainty provides greater freedom is discussed and the overcoming of capricious conscience and the pretension of absolute autonomy is proposed. It is argued that the moral subject, in order to be such, must go out to meet the other, through recognition, and overcome presentism, anthropocentrism, androcentrism and colonial thought.
Keywords: ethics; moral; higher education; values; socio-moral formation